Proposal for the control of Maternal Mortality in the Ancash Region, 2019 - Acosta-Yparraguirre, Linda Rocío (2021)
Introduction: Study proposed as a Macroproject based on the Theory of three delays, sociocritical paradigm, research-action: Maternity and healthy childhood projects to validate the proposal. Serious problem of public health, human rights and justice. Worldwide, 830 women die daily from preventable causes, being a priority of health policies contained in the Sustainable Development Goals. Objective: Design a Proposal for maternal mortality control in the Ancash Region. Materials and Methods: Applied, purposeful, retrospective, comparative, quantitative level. It used a validated registry card, population: 11 documents: three studies of maternal mortality, adolescent pregnancy, two reports: Right to safe motherhood, four national plans and Law No. 29409. Level II-2 hospitals were compared: Regional Eleazar Guzmán Barrón (HREGB ) and La Caleta (HLC), period 2006-2015, technique: documentary analysis and descriptive statistics. Previously, epidemiological and clinical characteristics, sociodemographic and obstetric causal factors were determined. Results: HREGB maternal death: 59.3% and HLC: 40.7%; MMR: 66.0 MM x 100,000 NV, basic cause hypertensive disorder: 22.2%, hemorrhage and non-obstetric sepsis: 18.5%; type of death: direct 66.7%; reproductive moment: pregnancy 59.3% and puerperium 37.0%; age: 25-29 years and 30-34: 29.6%; education: secondary 51.9%; cohabiting 44.4%; occupation: housework 81.5%; origin: urban 44.4%; multiparous 29.6%; 48.1% multigesta; prenatal care <6: 77.8%; and without contraception: 55.6%. Causal factors: lack of family and State protection; failure to identify warning signs, lack of self-determination, delays in emergency care: transfer and hospital care; marital status, occupation, pregnancy, prenatal care and completion of pregnancy. Conclusions: The proposal contains: multisectoral and interdisciplinary intervention for training of obstetricians, teachers and vulnerable population: pregnant women with high social risk and public policies for the protection of pregnant women by their partner, family, community and State. Legislative Proposal that extends paternity leave - Law No. 29409 amended by Law No. 30807.